The Influence of Promotion on the Purchase Decision of Mosque Dome (Case Study at PT. Anugerah Kubah Indonesia) (Proceeding of International Conference on Islamic Economics, Islamic Banking, Zakah and Waqf, 2023)
AbstractPromotional activities are activities that are very important for companies in order to introduce products. The ultimate goal is for consumers to purchase products. This article discusses the effect of promotion on purchasing decisions for mosque domes at PT. Indonesian Dome Award located in Purwokerto Village, Kec. Ngadiluwih Regency Kediri. To determine this effect, this article uses a descriptive quantitative research approach. The analysis used simple linear correlation and regression with the help of the SPSS 24 application. The sample used was 109 people. The results of data processing revealed that promotional activities at PT. The Indonesian Dome Award is classified as good with an attractive promotional method and media. The response to consumer purchasing decisions is good, meaning that consumers have compatibility between themselves and the aspects owned by PT. Indonesian Dome Award. This condition is reinforced by data processing which states that the influence of the promotion variable on the dome purchase decision is 25.3%.Keyword: Promotion, purchase decision, mosque dome